DISTRIBUSI KARBOHIDRAT NETRAL PADA LAMBUNG DEPAN SAPI SUMBA ONGOLE (Bos indicus) - Amalo, Filphin Adolfin; Maha, Inggrid Trinidad; Selan, Yulfia N.; Amleni, Lucia D. (JURNAL KAJIAN VETERINER, 2021)
Sumba Ongole cattle (Bos indicus) is a superior livestock commodity in East Nusa Tenggara Province, especially on the island of Sumba. Cattle have a forestomach consisting of the rumen, reticulum, and omasum. This forestomach plays an important role in carbohydrate fermentation. This study aims to determine the distribution of neutral carbohydrates in the forestomach of Sumba Ongole cattle. Six samples of the rumen, reticulum, and omasum were collected from East Sumba Slaughter House. The tissue was fixed in formalin 10 %, continued with processed histologically and PAS staining. The result showed that neutral carbohydrates distributed in the tunica mucosa and tunica muscularis rumen, reticulum, and omasum with a weak (+) to strong (+++) reaction intensity staining. The factors that influence the difference in color intensity in each tunica of the rumen, reticulum, and omasum are related to the function and mucus secretion of each cell.